2022
DOI: 10.3390/jcdd9080280
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Monocyte Chemoattractant Protein-1 in Patients with Cardiogenic Shock Complicating Acute Myocardial Infarction Treated with Mild Hypothermia: A Biomarker Substudy of SHOCK-COOL Trial

Abstract: Background: There is evidence that monocyte chemoattractant protein-1 (MCP-1) levels reflect the intensity of the inflammatory response in patients with cardiogenic shock (CS) complicating acute myocardial infarction (AMI) and have a predictive value for clinical outcomes. However, little is known about the effect of mild therapeutic hypothermia (MTH) on the inflammatory response in patients with CS complicating AMI. Therefore, we conducted a biomarker study to investigate the effect of MTH on MCP-1 levels in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…High levels of angiopoietin-2 are independently associated with increased short- and long-term mortality risk [ 44 ]. Similarly, we have previously shown that monocyte chemoattractant protein-1 levels on admission may be associated with short-term mortality [ 45 ]. However, these studies all suffer from limitations such as single-center, inadequate sample size, and small number of events.…”
Section: Discussionmentioning
confidence: 94%
“…High levels of angiopoietin-2 are independently associated with increased short- and long-term mortality risk [ 44 ]. Similarly, we have previously shown that monocyte chemoattractant protein-1 levels on admission may be associated with short-term mortality [ 45 ]. However, these studies all suffer from limitations such as single-center, inadequate sample size, and small number of events.…”
Section: Discussionmentioning
confidence: 94%
“…Only when comparing patients with a dsDNA/DNase ratio above and below the empirical cut-off, significantly higher MCP-1 levels could be shown in the group with higher dsDNA burden after 24 h, whereas only a trend remained after 96 h. MCP-1 functions chemotactically and recruits monocytes to the affected tissue during inflammatory processes. Interestingly, Cheng et al demonstrated an association of higher MCP-1 levels and lower 30-day mortality in a cohort of cardiogenic shock patients after acute myocardial infarction [ 24 ]. Moreover, in their work, biomarker levels increased within the first three days, whereas a decreasing trend was observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, MCP-1 was recently shown to prime neutrophils for NET formation in a cohort of STEMI patients [ 25 ], highlighting a potential connection between both parameters also in CA patients. As mentioned above, balanced inflammation is certainly crucial for a beneficial outcome, which may also explain the different findings of various authors regarding the effect of elevated MCP-1 levels [ 24 , 26 ]. Importantly, patients with unfavorable outcome showed decreased DNase activity 96 h after ICU admission, suggesting that a decreased repair capacity might play a role in patients with poor outcome, in addition to increased inflammation and cell death.…”
Section: Discussionmentioning
confidence: 99%